Perancangan Design Mesin Pelontar Pakan Ikan Berbasis Mikrokontroler Arduino Mega 2560 - Malik Abdul Aziz; Bayu Aji Girawan; Joko Setia Pribadi; Fadillah; Mardiyana (Politeknik Negeri Cilacap, 2021)
Fish feeder machine is a machine designed to perform a feeding process that works automatically according to a predetermined feeding schedule, this machine can help improve efficiency both in terms of feed quantity and time in the feeding process. The purpose of designing and calculating machine elements in this Fish Feeder is to calculate parts of machine elements, determine the concept of machine design, draw machine drawing detail, and determine bill of material. The manufacture of this machine uses approach method of James H Earle and concept selection using the method of Stuart Pugh, drawing software using Solidworks 2015 and working drawing using ISO Standard. The design of the throwing machine that has been made is the result of a literature approach and field surveys (direct surveys at the Fisheries Service and at the Fish Seed Center where fish feed throwing machines are needed). This machine needs a continuous process of development and testing